Man with a pan : culinary adventures of fathers who cook for their families - Donohue, John, 1968- (Algonquin Books of Chapel Hill, 2011)
"Look who's making dinner! Twenty-one of our favorite writers and chefs expound upon the joys--and perils--of feeding their families. Mario Batali's son boasts a preference for duck testicles. Peter Kaminsky's daughters won't eat anything at all. Mark Bittman reveals the four stages of learning to cook. Mark Kurlansky would love a woman to feed him, just once. Jim Harrison shows how good food and wine trump expensive cars and houses. Jesse Sheidlower searches for words to describe his vegetarianism to his kids. And Stephen King offers tips about what to cook when you don't feel like cooking. More men cook now than ever before, and this is the first book to celebrate those good eggs who toil behind the stove, trying to nourish and please. Their culinary adventures are accompanied by over sixty family-tested recipes, time-saving tips, and cookbook recommendations as well as an array of New Yorker cartoons. Plus, there are interviews with homestyle heroes cooking all across America--a fireman from Brooklyn, a football coach in Atlanta, a lawyer in Philadelphia, a bond trader in Los Angeles. What emerges is a book not just about food but about our changing families. It offers a newfound community for any man who proudly dons an apron and inspiration for those who have yet to pick up the spatula. "--